2019
DOI: 10.5897/jeif2018.0940
|View full text |Cite
|
Sign up to set email alerts
|

Impact of credit risk on corporate financial performance: Evidence from listed banks on the Ghana stock exchange

Abstract: A bank's financial performance and survival can be threatened when there is an increased exposure to credit risk. On this basis, this study seeks to identify the factors that determine the level of bank credit risk and further estimates the effects of bank credit risk on corporate financial performance using financial data from banks on the Ghana Stock Exchange over a 15-year period from 2003 to 2017. Using the method of 2SLS, it was observed variables such as capital adequacy, operating efficiency, profitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The credit risk assessment is a process applied in all banks to evaluate the quality of credit applications and to decide whether a borrower is eligible to get a credit facility to mitigate the credit risk (Richard et al, 2019). Many researchers investigated corporate credit risk assessment and its importance in the banking sector.…”
Section: The Importance Of Corporate Credit Risk Assessmentmentioning
confidence: 99%
“…The credit risk assessment is a process applied in all banks to evaluate the quality of credit applications and to decide whether a borrower is eligible to get a credit facility to mitigate the credit risk (Richard et al, 2019). Many researchers investigated corporate credit risk assessment and its importance in the banking sector.…”
Section: The Importance Of Corporate Credit Risk Assessmentmentioning
confidence: 99%
“…The general empirical studies on the Ghana Stock Exchange (GSE) have mainly focused on the performance of the listed firms with few emphases on the efficiency of the market and the possible contribution to economic growth. A corporate financial performance review on GSE-listed banks indicates that the bank's internal variables tend to increase profitability (Oduro et al, 2019) while the unlisted banks' financial performance is inverse with the level of leverage (Gadzo and Asiamah, 2018). With regards to market efficiency, the GSE is not efficient due to high transactional cost, low firm participation, and slow market competition (Ayentimi et al, 2013).…”
Section: Emperical Reviewmentioning
confidence: 99%
“…While some of them found negative relationships between the variables, others found positive relationships. For instance, Gadzo, Oduro, and Asiedu (2019) examined the influence of credit risk management on the performance of banks listed on the Ghana Stock Exchange. The outcome of that study showed that an inverse relationship existed between bank size, financing gap and credit risk management.…”
Section: Empirical Reviewmentioning
confidence: 99%